Subjects and Organizational Cultures of Foreign Companies (2019)
"Analysis of the relationship established by some subjects with the organizational cultures of foreign multinationals operating in Medellin", is a qualitative social research about the cultural impact that some multinationals have in Antioquia through its organizational influence. As main theoretical reference, it takes some psychoanalytic concepts such as subjectivity, identification and subject. At the end of the article, preceded by a description of the corresponding information analysis, some preliminary considerations about the relationship established by the interviewees with the organizational cultures of several multinational companies are presented.